THE APPLICATION OF PLATELET-RICH PLASMA (PRP) IN AESTHETIC TREATMENTS: A CONTEMPORARY FIQH PERSPECTIVE - Arif, Achmad; Kanggas, Fazari Zul Hasmi; Rachmawati, Andini; Hidayati, Rosidah; Kurniawan, Cecep Soleh (Jurnal Al-Dustur, 2025)
Platelet-Rich Plasma (PRP) treatment has gained significant attention as a cosmetic procedure in recent years, becoming a sought-after method for enhancing skin quality. Offered extensively in beauty clinics, both men and women pursue PRP treatment to reduce wrinkles, improve facial scars, and achieve a more youthful radiance. This procedure involves drawing a patient’s blood, processing it to isolate the plasma, and then injecting it into the facial area to stimulate collagen production and skin rejuvenation. This study explores the practice of PRP treatment in beauty clinics and examines its legal status from the perspective of contemporary Islamic jurisprudence (fiqh). Using a qualitative descriptive method and a library research approach, it analyzes primary sources such as the Qur’an, Hadith, and classical Islamic texts, complemented by secondary sources including modern scholarly literature. The research aims to assess whether PRP treatment aligns with Islamic ethical and legal principles. Findings indicate that, according to contemporary fiqh, PRP treatment performed for non-essential (tahsiniy) cosmetic purposes is deemed impermissible (haram). However, when used for medical or necessary (dharuriy) purposes, such as treating severe skin conditions or injuries, it may be considered permissible. This conclusion is drawn from scholarly ijtihad, fatwas issued by the Indonesian Council of Ulama (MUI), and the principles of Maqasid al-Shariah. The study highlights the need for further scholarly discourse to establish clear legal guidelines regarding PRP treatment, ensuring a well-informed approach that aligns with Islamic principles.